Who is a Jew? : reflections on history, religion, and culture - Greenspoon, Leonard J. (Leonard Jay) (Studies in Jewish civilization., 2014)
Jewish identity is a perennial concern, as Jews seek to define the major features and status of those who "belong," while at the same time draw distinctions between individuals and groups on the "inside" and those on the "outside." From a variety of perspectives, scholarly as well as confessional, there is intense interest among non-Jewish and Jewish commentators alike in the basic question, "Who is a Jew?"This collection of articles draws diverse historical, cultural, and religious insights from scholars who represent a wide range of academic and theological disciplines. Some of the authors d